Full-length huntingtin is palmitoylated at multiple sites and post-translationally myristoylated following caspase-cleavage - Lemarié, Fanny L.; Sanders, Shaun S.; Nguyen, Yen; Martin, Dale D. O.; Hayden, Michael R. (Frontiers in Physiology, 2023)
Huntington disease is an autosomal dominant neurodegenerative disorder which is caused by a CAG repeat expansion in the HTT gene that codes for an elongated polyglutamine tract in the huntingtin (HTT) protein. Huntingtin is subjected to multiple post-translational modifications which regulate its cellular functions and degradation. We have previously identified a palmitoylation site at cysteine 214 (C214), catalyzed by the enzymes ZDHHC17 and ZDHHC13. Reduced palmitoylation level of mutant huntingtin is linked to toxicity and loss of function. Moreover, we have described N-terminal myristoylation by the N-myristoyltransferases of a short fragment of huntingtin (HTT553-586) at glycine 553 (G553) following proteolysis at aspartate 552 (D552). Here, we show that huntingtin is palmitoylated at numerous cysteines: C105, C433, C3134 and C3144. In addition, we confirm that full-length huntingtin is cleaved at D552 and post-translationally myristoylated at G553. Importantly, blocking caspase cleavage at the critical and pathogenic aspartate 586 (D586) significantly increases post-translational myristoylation of huntingtin. In turn, myristoylation of huntingtin promotes the co-interaction between C-terminal and N-terminal huntingtin fragments, which is also protective. This suggests that the protective effect of inhibiting caspase-cleavage at D586 may be mediated through post-translational myristoylation of huntingtin at G553.